An epidemiological study of filariasis in a village of district Datia, MP - Mishra Ashok; Bhadoriya Rahul (Wolters Kluwer Medknow Publications, 2009)
Background: District Datia has been known to be endemic for filariasis. A number of cases have been reported in recent past. The present study was an epidemiological investigation carried out in village Barganya, Datia in the month of Sept 2004. Aims and Objectives: The objectives of this study were to confirm the epidemic in village Barganya and to study the causes of the present epidemic. Materials and Methods: The study was a cross sectional study carried out through house to house survey, covering a population of 1512. Result: A total of 78 clinically confirmed cases were reported. The study calculated a microfilarial rate of 6.9 % and 1.65% in males and females respectively. The microfilarial density among confirmed cases ranged from 3.1 to 10.6 per 20 cmm. Conclusion: The study concluded that majority of the cases were males who worked in open field and there was a lack of proper management of these cases at village level.